Quantitative Analysis of Matrine in Liquid Crystalline Nanoparticles by HPLC - Xinsheng Peng; Baohong Li; Min Hu; Yahao Ling; Yuan Tian; Yanxing Zhou; Yanfang Zhou (Journal of Analytical Methods in Chemistry)
A reversed-phase high-performance liquid chromatographic method has been developed to quantitatively determine matrine in liquid crystal nanoparticles. The chromatographic method is carried out using an isocratic system. The mobile phase was composed of methanol-PBS(pH6.8)-triethylamine (50 : 50 : 0.1%) with a flow rate of 1 mL/min with SPD-20A UV/vis detector and the detection wavelength was at 220 nm. The linearity of matrine is in the range of 1.6 to 200.0 μg/mL. The regression equation is y=10706x-2959 (R2=1.0). The average recovery is 101.7%; RSD=2.22%  (n=9). This method provides a simple and accurate strategy to determine matrine in liquid crystalline nanoparticle.